Analysis Of Suitability And Availability Of Plantation Land In Kombi District - Loho, Eureka M. I. Z.; Ngangi, Charles Reijnaldo; Kaunang, Rine (Jurnal Agroekoteknologi Terapan, 2024)
Analysis of the suitability and availability of plantation land for the RTRW in Kombi District as a research objective. Techniques for collecting data in the form of observations and agency surveys from October 2023 to January 2024. Data analysis used the Geographic Information System (GIS) ESRI ArcGIS 10.8 software with map overlay analysis techniques. The research results showed that 1) analysis of the suitability of plantation land use for RTRW in Kombi District shows that land suitability in Kombi District has five classifications, namely the "Potential Supporting" classification. And Not a Plantation Area" with an area of 4,254.07 Ha or 31% of the total area of the sub-district, classification "Suitable" with an area of 4,108.41 Ha or 30.41% of the total area of the sub-district, classification "Not Suitable" with an area of 2,653.50 Ha or 19.64% of the total area of the sub-district, the classification "Supporting Suitable (Potential Suitable)" with an area of 2,480.22 Ha or 18.36% of the total area of the sub-district and finally the classification of "Inland Waters" with an area of 16.03 Ha or 0 .12% of the total area of the sub-district. This shows that in Kombi sub-district there are 4,254.07 Ha of plantation land that is in accordance with its designation, but there are still 2,653.50 Ha of plantation land that is not in accordance with its land designation. 2) The results of the analysis of plantation land availability in Kombi District show that land availability in Kombi District has four classifications, namely the "Available" classification with an area of 6,588.63 Ha or 48.76% of the total area of the subdistrict, the "Not Available" classification with an area of 4,293, 30 Ha or 31.77% of the total area of the sub-district, classification "Not Plantation" with an area of 2614.28 Ha or 19.35% of the total area of the sub-district, classification of "Inland Waters" with an area of 16.03 Ha or 0.12% of total area of the district. This shows that in Kombi District there are 6,588.63 Ha of land available to become a plantation area and 4,293.30 Ha of land that is not available to become a plantation area. Keywords: Suitability and availability of land, Plantation, Kombi District, Minahasa regency. Abstrak Analisis kesesuaian dan ketersediaan lahan perkebunan terhadap RTRW di Kecamatan Kombi sebagai tujuan penelitian. Teknik dalam pengambilan data dalam bentuk observasi dan survey instansi pada bulan Oktober 2023 hingga bulan Januari 2024. Analisis data menggunakan Sistem Informasi Geografis (SIG) software ESRI ArcGIS 10.8 dengan teknik analisis overlay peta. Hasil penelitian didapatkan bahwa 1) analisis kesesuaian penggunaan lahan perkebunan terhadap RTRW di Kecamatan Kombi menunjukkan bahwa kesesuaian lahan di Kecamatan Kombi memiliki lima klasifikasi yaitu klasifikasi “Potensi Mendukung Dan Bukan Kawasan Perkebunan” dengan luas 4.254,07 Ha atau 31% dari total luas kecamatan, klasifikasi “Sesuai” dengan luas 4.108,41 Ha atau 30,41% dari total luas kecamatan, klasifikasi “Tidak Sesuai” dengan luas 2.653,50 Ha atau 19,64% dari total luas kecamatan, klasifikasi “Mendukung Sesuai (Potensi Sesuai)” dengan luas 2.480,22 Ha atau 18,36% dari total luas kecamatan dan yang terakhir klasifikasi “Perairan Darat” dengan luas 16,03 Ha atau 0,12% dari total luas kecamatan. Hal ini menunjukan bahwa di kecamatan kombi terdapat 4.254,07 Ha lahan perkebunan yang telah sesuai dengan peruntukannya namun masih terdapat 2.653,50 Ha lahan perkebunan yang tidak sesuai dengan peruntukan lahannya. 2) Hasil analisis ketersediaan lahan perkebunan di Kecamatan Kombi menunjukan bahwa ketersediaan lahan di Kecamatan Kombi memiliki empat klasifikasi yaitu klasifikasi “Tersedia” dengan luas 6.588,63 Ha atau 48,76% dari total luas kecamatan, klasifikasi “Tidak Tersedia” dengan luas 4.293,30 Ha atau 31,77% dari total luas kecamatan,  klasifikasi “Bukan Perkebunan” dengan luas 2614,28 Ha atau 19,35% dari total luas kecamatan, klasifikasi “Perairan Darat” dengan luas 16,03 Ha atau 0,12% dari total luas kecamatan. Hal ini menunjukan bahwa di Kecamatan Kombi terdapat 6,588,63 Ha lahan yang tersedia untuk menjadi kawasan perkebunan dan 4.293,30 Ha lahan yang tidak tersedia untuk dijadikan kawasan perkebunan. Kata kunci: Kesesuaian dan ketersediaan lahan, Perkebunan, Kecamatan Kombi, Kabupaten Minahasa